Detection of Paenibacillus larvae subsp. larvae spores in Brazil - Schuch, Dulce Maria Tocchetto; Tochetto, Lisane Goldmeier; Sattler, Aroni (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to detect the presence of Paenibacillus larvae subsp. larvae spores in products from a warehouse located in Rio Grande do Sul State, Brazil, the identification of possible contamination sources, and the assessment of spores transference possibility from contaminated imported products from the warehouse to apiaries located in the surrounding area. Samples of imported pollen and bulk honey stocked in the warehouse, and honeycomb (brood, honey and pollen) from a healthy hive, honey from one apiary and adult bees were analyzed. Imported honey and pollen, and three groups of adult bees and the honey collected from the honeycomb resulted positive.
Keywords: Apis mellifera; honey; pollen; contamination; hives